2D Polarized Materials: Ferromagnetic, Ferrovalley, Ferroelectric Materials, and Related Heterostructures. Issue 5 (16th December 2020) - Chu, Junwei; Wang, Yang; Wang, Xuepeng; Hu, Kai; Rao, Gaofeng; Gong, Chuanhui; Wu, Chunchun; Hong, Hao; Wang, Xianfu; Liu, Kaihui; Gao, Chunlei; Xiong, Jie
Abstract: The emergence of 2D polarized materials, including ferromagnetic, ferrovalley, and ferroelectric materials, has demonstrated unique quantum behaviors at atomic scales. These polarization behaviors are tightly bonded to the new degrees of freedom (DOFs) for next generation information storage and processing, which have been dramatically developed in the past few years. Here, the basic 2D polarized materials system and related devices' application in spintronics, valleytronics, and electronics are reviewed. Specifically, the underlying physical mechanism accompanied with symmetry broken theory and the modulation process through heterostructure engineering are highlighted. These summarized works focusing on the 2D polarization would continue to enrich the cognition of 2D quantum system and promising practical applications. Abstract : The distinct physical origin of 2D polarizations and modulation on degrees of freedom are comprehensively summarized based on the hysteresis behaviors and interface effects. The novel multifunctional polarized devices are discussed, from which perspectives and guidelines are proposed for developing "beyond Moore" integrated devices and circuits.